2023
DOI: 10.1371/journal.pcbi.1010781
|View full text |Cite
|
Sign up to set email alerts
|

Complex spatiotemporal oscillations emerge from transverse instabilities in large-scale brain networks

Abstract: Spatiotemporal oscillations underlie all cognitive brain functions. Large-scale brain models, constrained by neuroimaging data, aim to trace the principles underlying such macroscopic neural activity from the intricate and multi-scale structure of the brain. Despite substantial progress in the field, many aspects about the mechanisms behind the onset of spatiotemporal neural dynamics are still unknown. In this work we establish a simple framework for the emergence of complex brain dynamics, including high-dime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 121 publications
2
2
0
Order By: Relevance
“…Nonetheless, the improved understanding of how dynamic network instabilities arise in simplified systems acquired from this study provides a solid foundation for the future analysis of the dynamic behaviour of these more complicated networked systems. Note that a recent study by Clusella et al [39] discovered outcomes comparable to those demonstrated in this work for large-scale brain models without delay. In particular, the authors in [39] proposed that transverse instabilities in the synchronization manifold provide a possible mechanism underlying experimentally observed spatio-temporal neural activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, the improved understanding of how dynamic network instabilities arise in simplified systems acquired from this study provides a solid foundation for the future analysis of the dynamic behaviour of these more complicated networked systems. Note that a recent study by Clusella et al [39] discovered outcomes comparable to those demonstrated in this work for large-scale brain models without delay. In particular, the authors in [39] proposed that transverse instabilities in the synchronization manifold provide a possible mechanism underlying experimentally observed spatio-temporal neural activity.…”
Section: Discussionsupporting
confidence: 87%
“…Note that a recent study by Clusella et al [39] discovered outcomes comparable to those demonstrated in this work for large-scale brain models without delay. In particular, the authors in [39] proposed that transverse instabilities in the synchronization manifold provide a possible mechanism underlying experimentally observed spatio-temporal neural activity. Given the results presented here, it would be fascinating to investigate how the presence of delays affects dynamic brain network models.…”
Section: Discussionsupporting
confidence: 87%
“…While there have been explorations of clearly characterized aerial-view spatial phenomena such as, e.g. traveling waves, in BOLD fMRI [33][34][35][36][37][38][39][40][41][42][43][44][45][46], more granular, data-driven analyses of local directional flows and their larger propagative implications have not been reported in the fMRI literature. The methods we present below are a first step toward addressing a potentially important and long-neglected aspect of the BOLD signal.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have used data-driven approaches to identify and characterize whole-brain states that occur in a variety of task environments from more traditional "stimulus-response" type paradigms to passive viewing of lengthy movie clips (Nastase et al, 2021;Saarimäki, 2021;Simony & Chang, 2020). While it is now well-accepted in the EEG literature that the brain appears to traverse through several states during a single trial (Clusella et al, 2023;Kringelbach & Deco, 2020), research in functional connectomics, too, has also modeled "resting" fMRI data as dynamic, whole-brain connectomic states (Allen et al, 2014;Ciric et al, 2017) in part because the distribution of these states may carry clinically-relevant diagnostic information (Damaraju et al, 2014;Reinen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%